1999
DOI: 10.1002/(sici)1096-8628(19991029)86:5<427::aid-ajmg6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cerebral infarctions and del(10)(p14p15.1) de novo in HDR (hypoparathyroidism, sensorineural deafness, renal dysplasia) syndrome

Abstract: We report on a Japanese boy with HDR syndrome (hypoparathyroidism, sensorineural deafness, renal dysplasia) and recurrent cerebral infarctions in the basal ganglia. The patient experienced cerebral infarctions four times between age 7 months and age 20 months. Chromosome analysis of the patient demonstrated a 46,XY, del(10)(p14p15.1) de novo. This suggests that the putative gene responsible for HDR syndrome is located at 10p14-p15.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, as depicted in Figure 2, the predicted amino acid sequence is quite different from those of wild type homologous/orthologous genes. In addition, the association of neurological complications, such as repetitive cerebral infarctions, with a GAT A3 gene mutation has also been reported 14 . In Figure 1, the hitherto reported mutations in the GATA3 gene are summarized 3 " 7 , and it is apparent that the 405insC mutation is the first to destroy the entire TA2 domain (and two zinc fingers).…”
Section: Discussionmentioning
confidence: 97%
“…However, as depicted in Figure 2, the predicted amino acid sequence is quite different from those of wild type homologous/orthologous genes. In addition, the association of neurological complications, such as repetitive cerebral infarctions, with a GAT A3 gene mutation has also been reported 14 . In Figure 1, the hitherto reported mutations in the GATA3 gene are summarized 3 " 7 , and it is apparent that the 405insC mutation is the first to destroy the entire TA2 domain (and two zinc fingers).…”
Section: Discussionmentioning
confidence: 97%
“…In 1992, Bilous et al [1] described two brothers and two daughters of one of the affected brothers with hypoparathyroidism, sensorineural deafness, and renal dysplasia. Subsequently, other reports appeared in the literature confirming that the syndrome is associated with a wide phenotype spectrum, consisting of hypoparathyroidism, sensorineural deafness, and renal disease [4, 7, 9, 13, 14]. Patients may present with hypocalcemia, tetany, or afebrile convulsions at any age.…”
Section: Discussionmentioning
confidence: 99%
“…Hasegawa et al [7] found reports of 14 patients with deletion of 10p13; five had hypoparathyroidism or hypocalcemia, 6 had urinary tract abnormalities, and 2 had deafness. Fujimoto et al [9] reported a Japanese boy with associated recurrent cerebral infarctions in the basal ganglia. Lichtner et al [15] performed molecular deletion analysis of two patients with partial monosomy 10p and hypoparathyroidism, deafness and renal dysplasia, or renal insufficiency, cardiac defect, cleft palate, and reduced T-cell levels.…”
Section: Discussionmentioning
confidence: 99%
“…The sensorineural hearing loss in HDR patients can be both symmetric or asymmetric, and as tested by auditory brainstem response (ABR), conditioned orientation reflex tests or pure tone audiometry, it ranges in level from 40 dB to 105 dB (Bilous et al, 1992;Fujimoto et al, 1999;Hasegawa et al, 1997;Lichtner et al, 2000;Muroya et al, 2001). Although it is clear that hearing loss in HDR is usually somewhat more severe at the higher end of the frequency spectrum Muroya et al, 2001), no systematic audiometric evaluation has yet been made, and the exact pathophysiological mechanism causing the hearing defect remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%